2010
DOI: 10.1002/hpm.988
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the funds in the New Cooperative Medical Scheme in rural China: determinants and influencing factors in two provinces

Abstract: In recent years, the central government in China has been leading the re-establishment of its rural health insurance system, but local government institutions have considerable flexibility in the specific design and management of schemes. Maintaining a reasonable balance of funds is critical to ensure that the schemes are sustainable and effective in offering financial protection to members. This paper explores the financial management of the NCMS in China through a case study of the balance of funds and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Though subsidized heavily by the central government, the NCMS does not have a one-size-fits-all detailed plan for implementation across the country except for a couple of principles. Operated by county administrations, the NCMS benefit package and payment methods vary from area to area [18-21]. Such institutional arrangements may offer flexibility in resource allocation and the opportunity for management innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Though subsidized heavily by the central government, the NCMS does not have a one-size-fits-all detailed plan for implementation across the country except for a couple of principles. Operated by county administrations, the NCMS benefit package and payment methods vary from area to area [18-21]. Such institutional arrangements may offer flexibility in resource allocation and the opportunity for management innovation.…”
Section: Introductionmentioning
confidence: 99%
“…During the initial phases of implementation, many NCMS management teams were concerned about exhausting annual revenues and worked vigorously to build reserves. A case study on the financial management of the NCMS in six counties in two Chinese provinces found that five out of six held a large fund surplus, while their enrollees obtained only partial financial protection [29]. In order to reduce schemes surpluses, some counties will do a second round reimbursement usually at the end of a year.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the NCMS should extend its benefits to migrants. In reality, however, the opportunities to sustainably increase the financial protection offered to NCMS enrollees are limited by the financial pressures on local governments [29]. Poor rural counties have very limited resources to support coverage of health care in expensive urban hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Although coverage and the utilization of medical services has increased, and the costs of care have been reduced, out-of-pocket expenses for medical treatment is still a significant financial burden for many rural households (Sun, Jackson, Carmichael, & Sleigh, 2009). The government is aware of the problem and has indicated that it will improve the management capacity of the scheme and also review its overall policy design (Zhang et al, 2010) There have been somewhat similar developments with the introduction of a rural social retirement pension scheme, which was originally dismantled but is now being reintroduced. In the mid 1980s, as the numbers of elderly people in financial need increased, the government examined the need for a social insurance pension system in the rural areas.…”
Section: Social Insurancementioning
confidence: 91%